Microwave-assisted extraction of eco-friendly surfactant from Jatropha curcas for sustainable solubilization of reactive dyes - Aryanti, Nita; Nafiunisa, Aininu; Ratnawati; Widiasa, I Nyoman; Zakki, Abdurrahman; Adina, Alifia Rizki; Khoiriyah, Lu'luatul (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2025)
Natural surfactants derived from plant-based sources, such as saponins, remain underexplored. This study developed the extraction of saponins from Jatropha curcas leaves using microwave-assisted extraction (MAE) finding that the optimized condition of 3 min, 363.15 K, 30 mL/g ratio of extraction yielded the highest saponin content of 35.04 mg/g. The FTIR and HPLC analyses confirmed the structural similarity between the extract and commercial saponin. Additionally, the extracted saponins effectively solubilized Remazol Red RB and Blue TQ with solubilization efficiency increasing proportionally to the surfactant concentration. The surfactant properties of the extracted saponin were also confirmed by its ability to form foam and high critical micellar concentration, which revealed the potential for material valorization. This work demonstrated that the development of plant-based surfactants provides a sustainable alternative to synthetic surfactants. Moreover, valorizing natural materials contributes to the advancement of eco-friendly technologies, particularly in waste treatment and water purification applications.